2020
DOI: 10.1177/1177271920976367
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers: Our Path Towards a Cure for Alzheimer Disease

Abstract: Over the last decade, biomarkers have significantly improved our understanding of the pathophysiology of Alzheimer disease (AD) and provided valuable tools to examine different disease mechanisms and their progression over time. While several markers of amyloid, tau, neuronal, synaptic, and axonal injury, inflammation, and immune dysregulation in AD have been identified, there is a relative paucity of biomarkers which reflect other disease mechanisms such as oxidative stress, mitochondrial injury, vascular or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 236 publications
(367 reference statements)
0
30
0
Order By: Relevance
“…Up to now, however, the results of clinical trials to evaluate the state of the AD therapy have been disappointing. In the future, development should be based on multiple criteria, including the state of the disease, its progression, and the activity of biomarkers focused on critical processes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, however, the results of clinical trials to evaluate the state of the AD therapy have been disappointing. In the future, development should be based on multiple criteria, including the state of the disease, its progression, and the activity of biomarkers focused on critical processes [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although incomplete, the present knowledge appears of interest to establish the properties of some AD heterogeneous forms, such as responses to treatments. The study of multiple biomarkers, identified during the last months, might be sufficient to characterize at clinical level various aspects of AD, including diagnosis and prognosis [ 38 , 39 , 40 ]. Heterogeneity exists also for tau.…”
Section: Ad and Its Multiple Fluid Biomarkersmentioning
confidence: 99%
“…Historically, abnormal accumulation of fibrillar amyloid plaques in the extra-neuronal compartment – amyloidosis – has been the key lesion described in AD. Such amyloid plaques dysregulate neuronal connections, increase cerebral oxidative stress, enhance cerebral inflammation and cerebral amyloid angiopathy, and ultimately lead to neuronal apoptosis ( Tarawneh, 2020 ).…”
Section: Stress Depression and Alzheimer's Disease: A Bio-continuummentioning
confidence: 99%
“…These biomarkers exhibit greater than 95% sensitivity and 85% specificity in regards to diagnosing AD. 2 Low quantities of Aβ42 in the CSF are observed in AD individuals compared to controls, 29 while elevated levels of hyper-phosphorylated tau and t-tau have been identified in the CSF in AD patients. 2, 30 Previous literature has shown that high t-tau and/or p-tau181 along with low Aβ42 in the CSF can be detected before patients with AD become symptomatic, and offer improved diagnostic accuracy of AD from other causes of dementia.…”
Section: Cerebrospinal Fluid (Csf) Biomarkersmentioning
confidence: 99%
“…The most promising biomarkers associated with synaptic dysfunction in AD patients are the postsynaptic protein neurogranin (Ng) and the presynaptic proteins synaptosome-associated protein-25 (SNAP25) and synaptotagmin-1 (Syt1). 2 The overall neuronal specificity and abundant expression of Ng, SNAP25, and Syt1 allow these biomarkers to accurately reflect the degree of neuronal and synaptic injury. This is because the CSF level of these biomarkers correlate with damage to neuronal and synaptic structures, as well as with the release of neuronal or synaptic components into the extracellular compartment as neurodegeneration progresses.…”
Section: Synaptic Biomarkersmentioning
confidence: 99%